2012
DOI: 10.1111/j.1463-6409.2012.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a revised Amphinomidae (Annelida, Amphinomida): description and affinities of a new genus and species from the Nile Deep‐sea Fan, Mediterranean Sea

Abstract: Rouse, G.W. (2012). Towards a revised Amphinomidae (Annelida, Amphinomida): description and affinities of a new genus and species from the Nile Deep-sea Fan, Mediterranean Sea. -Zoologica Scripta, 41, 307-325. The discovery of a new amphinomid species from wood falls deployed near cold seeps (1694 m) at the Nile Deep-sea Fan (Mediterranean Sea) highlights the need to revise Amphinomidae to better characterize amphinomid diversity. The phylogenetic affinities of the new amphinomid and 12 other species from nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 45 publications
7
60
0
1
Order By: Relevance
“…Previously published data from Crete, Malta, Gulf of Mexico, Caribbean Sea and Gulf of Guinea were also included in the analyses (Ahrens et al, 2013, with accession numbers: Crete KC017526-8, 30; Malta KC017553-56; Caribbean Sea KC017521,24-25, KC017552; Gulf of Mexico KC017587-90 and Gulf of Guinea KC0 17480-2, KC017569). Taking into account the high rates (around 30%) of the genetic distances observed among other amphinomid genera (e.g., Borda et al, 2012) no out-group could be selected for the phylogenetic analyses. Therefore, the tree constriction midpoint rooted technique was selected, following Ahrens et al (2013).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Previously published data from Crete, Malta, Gulf of Mexico, Caribbean Sea and Gulf of Guinea were also included in the analyses (Ahrens et al, 2013, with accession numbers: Crete KC017526-8, 30; Malta KC017553-56; Caribbean Sea KC017521,24-25, KC017552; Gulf of Mexico KC017587-90 and Gulf of Guinea KC0 17480-2, KC017569). Taking into account the high rates (around 30%) of the genetic distances observed among other amphinomid genera (e.g., Borda et al, 2012) no out-group could be selected for the phylogenetic analyses. Therefore, the tree constriction midpoint rooted technique was selected, following Ahrens et al (2013).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Protocols for whole genomic DNA extraction, amplification and sequencing procedures are as reported by Borda et al [45], unless stated otherwise. Electronic supplementary material , table S2 lists primers and annealing temperature profiles used for amplification of mt cytochrome c oxidase subunit I (COI), and mt 16S rDNA (16S).…”
Section: Methodsmentioning
confidence: 99%
“…Electronic supplementary material , table S2 lists primers and annealing temperature profiles used for amplification of mt cytochrome c oxidase subunit I (COI), and mt 16S rDNA (16S). Amplification protocols for the nuclear internal transcribed spacer 1 (ITS1) and 28S rDNA (28S) followed Nygren & Pleijel [46] and Borda et al [45], respectively. All data were analysed using maximum-likelihood (ML) and Bayesian inference (BI) procedures following methods described in [45], as was the choice of outgroup to root the analyses (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This species has been widely recorded from the region in ecological and in popular articles but recent studies by Barroso et al (2010) and Borda et al (2012) would suggest that the species actually represent a suites of species and it is probable that E. complanata is restricted to the Caribbean and not the widespread "cosmopolitan" species as has previously been reported.…”
Section: Genus Eurythoe Kinberg 1857mentioning
confidence: 96%
“…It is suggested that this species identification which has not been formally published needs careful checking given the taxonomic problems of the family especially this supposedly widespread tropical species (Borda et al 2012).…”
Section: Family Amphinomidae Savigny In Lamarck 1818mentioning
confidence: 99%